Essays on Kant's anthropology - Jacobs, Brian (Brian Wallace); Kain, Patrick (Cambridge University Press, 2003)
Kant's lectures on anthropology capture him at the height of his intellectual power. They are immensely important for advancing our understanding of Kant's conception of anthropology. This collection of essays by some of the leading commentators on Kant offers the first systematic account of the philosophical importance of this material.